Social media and terrorism in Indonesia : enhancing or diluting its appeal? - Nur Azlin Mohamed Yasin (2012)
The online Bahasa Indonesia extremist community no longer exists exclusively in a world of its own, in password-protected forums. Members also participate in social media, exposing themselves to a wider audience and softening their extremist image. How does this affect the adherents of extremist ideology, and Indonesian society as a whole?